Semi-quantitative F-18-FDG PET/computed tomography parameters for prediction of grade in patients with renal cell carcinoma and the incremental value of diuretics. Issue 5 (May 2020) - Singh, Harpreet; Arora, Geetanjali; Nayak, Brusabhanu; Sharma, Akshima; Singh, Geetika; Kumari, Kalpana; Jana, Suman; Patel, Chetan; Pandey, Anil Kumar; Seth, Amlesh; Kumar, Rakesh
Abstract : Objective: The primary objective of the study was to evaluate the correlation between semi-quantitative F-18 FDG PET parameters and renal cell carcinoma (RCC) grade and its role in predicting the histopathological grade in RCC. The secondary objective was to evaluate the role of forced diuresis in improving the diagnostic accuracy of F-18 FDG for RCC. Methods: Thirty-three patients with radiologically proven RCC were included in the study. All patients underwent PET/CT on a dedicated PET/CT scanner (Biograph mCT; Siemens Medical Solutions, Erlangen, Germany) 45–60 min post-injection F-18-FDG. Patients were then injected 1 mg/kg body weight furosemide (upto 40 mg) and regional PET/CT images of abdomen were acquired after 2 h. For both baseline and post-diuretic F-18-FDG PET/CT scans, maximum standardized uptake value for tumor (SUVmax), mean SUV for tumor, metabolic tumor volume (MTV), tumor-to-liver (T/L) and tumor-to-kidney ratio (T/K) were calculated. Histopathology findings were considered as the reference standard. To assess the incremental value of diuresis in scan interpretation, visual analysis of scans was done. Results: Of 33 patients, histopathology grading was available for comparison with metabolic tumor markers in all except four. Of 29 patients (mean age = 51.89 ± 13.54 years), 20 patients had clear cell (cc) type while rest had non-cc RCC. Difference between the mean values among the categories was insignificant for all parameters except T/K. Fuhrman grading was obtained in 25 patients (17 low and eight high). SUVmax, MTV and T/L were found to be significantly different between low and high grade patients. Significantly strong positive correlation was observed between Furhman grades and tumor metabolism (r ≥ 0.5). No significant difference was observed between baseline and post-diuretic scan in any of the patients. Conclusion: Semi-quantitative F-18 FDG PET parameters (SUVmax, MTV and T/L) were found to be significantly correlated with Fuhrman grade in patients with RCC and are important markers for differentiation between low- and high-grade tumors. Furthermore, forced diuresis had no incremental value in characterization of primary RCC lesions.